Gold metallogeny of Australia - Rankine, Graham M (Rhodes University, Faculty of Science, Department of Geology, 1987)
The gold metallogeny of Australia is predominantly confined to the Archaean and Palaeozoic Provinces. The Archaean gold occurrences are predominantly hosted in ultramafic-mafic dominated greenstone belts, with less associated tofelsic-volcanic and sedimentary sequences. Most gold occurrences are confined to shear zones or faults, and adjacent discoveries of economic laterite-hosted deposits, host rocks. Recent are presently under investigation and will supply a significant proportion of production in the future. The Proterozoic gold deposits of Australia , are confined to geosyncinal sequences, commonly turbidites (eg: Telfer), with other hydrothermal deposits associated directly to granites. An important feature of the North Australian Craton deposits, is the spatial association of most deposits to granite bodies, although a genetic link has not been established conclusively. The Roxby Downs deposit in South Australia is a unique occurrence of gold in association to copper, uranium and R.E.E. This deposit is tentatively related to intraplate alkaline-magmatism, with further work necessary. The most significant recent discovery of gold mineralization in Australia is in the Drummond Basin in Queensland. This epithermal is tentatively related to mineralization within the Georgetown Inlier. The latter mineralization is Permo-Carboniferous, in a Proterozoic (and possibly Archaean) sequence of schists. It is tentatively suggested that all the gold mineralization in northern Queensland may be related to single tectonic event, a feature which requires further study . Other mineralization in the Phanerozoic includes the turbidite-hosted metamorphogenic deposits of Victoria, the rift related deposits in New South Wales and magmatic related deposits in Queensland. The gold deposits in Australia may in the future be classified in a tectonogeological framework, similiar to the layout of this dissertation, particularly once further data becomes available on recent discoveries.
Keywords: Gold ores -- Geology -- Australia; Gold mines and mining -- Australia; Gold -- Metallurgy -- Australia